2023
DOI: 10.1111/ejn.15937
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ventromedial hypothalamus activity during exposure to innate and conditioned threats

Abstract: In the face of imminent predatory danger, animals quickly detect the threat and mobilize key survival defensive actions, such as escape and freezing. The dorsomedial portion of the ventromedial hypothalamus (VMH) is a central node in innate and conditioned predator-induced defensive behaviours. Prior studies have shown that activity of steroidogenic factor 1 (sf1)-expressing VMH cells is necessary for such defensive behaviours. However, sf1-VMH neural activity during exposure to predatory threats has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Indeed, rat aggression towards mice is observed as predatory behaviour (Horovitz et al, 1966; Ilchibaeva et al, 2017; Tulogdi et al, 2015). In addition, close proximity to a rat elicits a flight response in mice (Deng et al, 2016; Esteban Masferrer et al, 2020; Reis, Lee, et al, 2021; Reis, Liu, et al, 2021; Tobias et al, 2023; Wang, Schuette, La‐Vu, et al, 2021; Wang, Schuette, Nagai, et al, 2021). Thus, this innate threat experience required BNST GABA neurons for the consequential behavioural response in post‐encounter foraging when the predator was no longer present.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, rat aggression towards mice is observed as predatory behaviour (Horovitz et al, 1966; Ilchibaeva et al, 2017; Tulogdi et al, 2015). In addition, close proximity to a rat elicits a flight response in mice (Deng et al, 2016; Esteban Masferrer et al, 2020; Reis, Lee, et al, 2021; Reis, Liu, et al, 2021; Tobias et al, 2023; Wang, Schuette, La‐Vu, et al, 2021; Wang, Schuette, Nagai, et al, 2021). Thus, this innate threat experience required BNST GABA neurons for the consequential behavioural response in post‐encounter foraging when the predator was no longer present.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that induction of robust freezing behavior is determined by a distinct set of VMH neurons, and the intensity of freezing behavior is encoded separately, possibly by the intensity or dynamics of the neuronal firing, which cannot be detected by the cFos-IR used in this study. The VMHdm/c region contains several subpopulations of neurons that coordinate various defensive behavioral responses (Engelke et al, 2021;Esteban Masferrer et al, 2020;Kennedy et al, 2020;Silva et al, 2016;Tobias et al, 2023). Previous studies have demonstrated that optogenetic stimulation of VMHdm/c neurons induces freezing/immobility responses, suggesting that these neurons mediate freezing behavior in response to predator cues (Kunwar et al, 2015;Wang et al, 2015).…”
Section: Differential Activation Of Vmh Neurons Potentially Underlyin...mentioning
confidence: 99%